2016
DOI: 10.1149/2.0381701jes
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for the Creation of a High Areal Capacity Lithium-Sulfur Battery Using a Metal Foam Current Collector

Abstract: A high areal capacity lithium-sulfur battery making use of mass produced aluminum metal foam as a current collector was investigated. A sulfur/Ketjenblack (KB) composite was filled and deposited into the aluminum foam current collector via a predetermined filling procedure, resulting in high sulfur loading. The value for this loading was found to be 17.7 mg sulfur/cm 2 by using carboxymethyl cellulose and styrene butadiene rubber (CMC + SBR) as a binder. An operating single-layer pouch-type cell with an S/KB-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…The increased interest in investigating practical battery conditions has resulted in improved sulfur loading (>10 mg cm −2 ), sulfur content (55–75 wt%), and low electrolyte/sulfur ratios (3–8) in lithium–sulfur cells reported in the last five years. Currently, more studies have demonstrated the intention of enhancing these key parameters in parallel (Table S1, Supporting Information), which we view as a positive trend in the field …”
Section: Extrinsic Challenges Of Fabricating High‐loading Sulfur Cathmentioning
confidence: 95%
See 1 more Smart Citation
“…The increased interest in investigating practical battery conditions has resulted in improved sulfur loading (>10 mg cm −2 ), sulfur content (55–75 wt%), and low electrolyte/sulfur ratios (3–8) in lithium–sulfur cells reported in the last five years. Currently, more studies have demonstrated the intention of enhancing these key parameters in parallel (Table S1, Supporting Information), which we view as a positive trend in the field …”
Section: Extrinsic Challenges Of Fabricating High‐loading Sulfur Cathmentioning
confidence: 95%
“…In 2017, Nara et al presented a comprehensive balance in the cathode with a sulfur loading of 17.7 mg cm −2 utilizing an electrolyte/sulfur ratio of just 2.7. These electrolyte/sulfur ratio calculations took into consideration the pore volume in the cathode and separator …”
Section: Extrinsic Challenges Of Fabricating High‐loading Sulfur Cathmentioning
confidence: 99%
“…12 Increasing the sulfur loading amount and reducing the electrolyte volume simultaneously is essential for practical applications of the Li-S battery, where an energy density of 300 Wh kg ¹1 is expected. 17 Three-dimensional (3D)-current collectors have been employed for increasing the sulfur loading, [18][19][20][21] but there has been limited success in simultaneously achieving reduction of the electrolyte amount. Furthermore, reducing the amount of conventional ether-based electrolytes that dissolve PS, such as 1 M Li-bis(trifluoromethane sulfonyl)amide (Li[TFSA]) in 1,3-dioxolane/1,2-dimethoxyethane (DOL/DME), leads to degradation of battery performance.…”
Section: Introductionmentioning
confidence: 99%
“…[37] To solve these issues, various 3D currentc ollectors have been in-vestigated, which allow ah igh sulfur loading, efficient charge transfer and long cycling stability. [37][38][39][40][41][42][43][44] However,t hese innovative structuresh ave some drawbacks, including:a )complex and expensive fabrication procedures that are difficult to scale up, b) as pecial sulfur introductions tep that is incompatible with traditional slurry preparation processes, c) the demand for large electrolyte volumet ow et the electrode, which sacrifices the overall energy density. [35,45] Current collectors that offset these shortfalls while maintaining some structural advantages are desirable.…”
Section: (B) Current Collectormentioning
confidence: 99%